The impact of Monkey Stories application on young leaners’ vocabulary acquisition - Syahria, Nukmatus; Azzaria, Syarifah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Vocabulary should be introduced from a young age so that children can master the target language. Digital games can help young learners learn a foreign language more effectively. This study aims to find the effectiveness of the Monkey Stories application on students’ vocabulary acquisition. This study applied an experimental design with one pre-test and a post-test design. The sample used was the fourth-graders of Semambung I Elementary School, Sidoarjo, with 30 learners as the experimental class and 30 learners as the control class. The data was analyzed by using the SPSS 26 version. The result showed that the students in the experimental group outperformed the students in the control group. The mean score of the post-test of the experimental group was 8,633, while the mean score of the post-test of the control group was 5,3. This study has valuable implications for teachers to create engaging and creative vocabulary learning environments for young learners so that they are motivated to learn Vocabulary to help them master the target language.